Recent Developments in the Irish Labour Market: Is It All Good News? - Elish Kelly; Alan Barrett (Institute of Labor Economics (IZA), 2017)
Across many countries, the rise of atypical work has been noted whereby employees are increasingly in less secure contractual situations. While this might lead to more flexible labour markets, there are potential downsides for individuals. We explore the prevalence of atypical work in Ireland which provides a fascinating case-study. Ireland experienced a dramatic deterioration in its labour market around the Great Recession with unemployment rising from 4.8 percent in 2007 to 15 percent in 2012. This situation was also reversed somewhat quickly with unemployment falling to 8 percent by 2016. Such dramatic swings provide the context in which we explore whether atypical work increased for new job holders with the onset of recession and whether or not this weakened as the economy recovered. We find that atypical work did increase with the recession and, although moderating, the likelihood of new jobs being atypical persisted into the recovery. This raises important questions about whether economic recovery alone will improve job quality, in addition to jobs numbers.
Keywords: J41; J48; 330; atypical work; temporary contracts; part-time; recession